2018
DOI: 10.1038/s41598-018-20178-7
|View full text |Cite
|
Sign up to set email alerts
|

Using Transfer Function Analysis to develop biologically and economically efficient restoration strategies

Abstract: Rare species across taxonomic groups and biomes commonly suffer from multiple threats and require intensive restoration, including population reintroduction and threat control. Following reintroduction, it is necessary to identify what level of threat control is needed for species to persist over time. Population reintroduction and threat control are time intensive and costly. Thus, it is pragmatic to develop economically efficient restoration strategies. We combined transfer function analysis and economic cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We also found that a three-fold increase in the probability of years with high seedling recruitment would be required for the D. waianaeensis reintroduction to persist over time (Figure 1B). A potential restoration strategy to increase the frequency of years with high seedling recruitment (i.e., 3 seedlings per reproductively mature plant) would be to suppress non-native frugivores and seedling herbivores (Bialic-Murphy et al, 2018). While our simulations provide insight into the population-level responses of increased seedling recruitment via pest control, many other exogenous factors can influence temporal variability in seedling recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also found that a three-fold increase in the probability of years with high seedling recruitment would be required for the D. waianaeensis reintroduction to persist over time (Figure 1B). A potential restoration strategy to increase the frequency of years with high seedling recruitment (i.e., 3 seedlings per reproductively mature plant) would be to suppress non-native frugivores and seedling herbivores (Bialic-Murphy et al, 2018). While our simulations provide insight into the population-level responses of increased seedling recruitment via pest control, many other exogenous factors can influence temporal variability in seedling recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The density of R. rattus can be highly variable from year to year and is a primary driver of temporal variability in seedling recruitment (Innes et al, 2001;Meyer and Butaud, 2009;Franklin, 2014). At our field site, R. rattus consume, on average, 83% of the mature fruits (Bialic-Murphy et al, 2018). Similarly, non-native molluscs decrease seedling density of endemic plants in Hawai'i by up to 33% (Kawelo et al, 2012).…”
Section: Study Speciesmentioning
confidence: 92%
See 2 more Smart Citations